Knowledge, attitude and self-efficacy of elderly caregivers in Chinese nursing homes: a cross-sectional study in Liaoning Province - Huijun Zhang; He Sun (BMJ Open)
Objective This study aimed to investigate the perceptions of elderly caregivers in Chinese nursing homes (NHs) and associated factors with regard to knowledge, attitude about elderly and self-efficacy.Setting A cross-sectional questionnaire survey was conducted in 12 NHs in Liaoning Province, China.Participants A total of 403 caregivers from 12 NHs were surveyed.Outcome measures Data were collected using a self-administered questionnaire composed of the Palmore’s Facts on Aging Quiz I, Kogan’s Attitude Towards Old People Scale, General Self-Efficacy Scale and background characteristics of participants. An average score for knowledge, attitude and self-efficacy was calculated. Differences across groups were evaluated using Student’s t-test and analysis of variance. Multivariable linear regression models were established to estimate the associated factors.Results The participating caregivers reported a relative low score on knowledge about the elderly (10.42±2.79), attitude towards old people (127.85±14.36) and self-efficacy (27.12±4.9). Multivariable regression analysis showed that respondents who had high educational level (β=0.212, 95% CI 0.193 to 0.824), received prejob training (β=0.193, 95% CI 0.081 to 1.169) and had high job satisfaction (general satisfaction: β=0.345, 95% CI 0.223 to 1.875; very satisfied: β=0.322, 95% CI 0.210 to 1.283) gave a positive rating on knowledge. Caregivers who were employed as formal staff (β=0.155, 95% CI 0.116 to 1.670), earned a high income (β=0.214, 95% CI 0.117 to 1.461) and had an interest in working with the elderly (β=0.141, 95% CI 0.088 to 1.508) tended to develop a positive attitude towards the elderly. However, caregivers who were female (β=−0.110, 95% CI −1.751 to −0.080) and had long work experience (β=−0.130, 95% CI −1.527 to −0.110) developed negative perception. Caregivers who were older (β=0.215, 95% CI 0.139 to 1.027), received prejob training (β=0.143, 95% CI 0.113 to 1.024), had an interest in working with the elderly (β=0.154, 95% CI 0.114 to 1.015), had high job satisfaction (β=0.177, 95% CI 0.116 to 1.223) and perceived better health status for the elderly (partial disability: β=0.437, 95% CI 0.259 to 1.600; no disability: β=0.288, 95% CI 0.153 to 1.211) gave a positive rating on self-efficacy.Conclusion Knowledge about the elderly, attitude towards old people and self-efficacy of elderly caregivers in Chinese NHs were at low levels. Some targeted intervention programmes, such as conducting professional training for aged care and a performance-based payment system, should be given priority to improve these attributes.